The role of lipid toxicity and para-inflammation as potential mechanisms of age related macular degeneration - Al-Rashed, Fatema (2016)
Age-Related Macular Degeneration (ARMD) is the most common cause of legal blindness in the elderly in the western world. One of the earliest signs of aging is the accumulation of lipid rich debris within and underneath the Retinal Pigmented Epithelium (RPE) cells, known as “drusen”. The disease is poorly understood - mainly because it occurs late in life as well as the lack of appropriate cell and animal models. RPE lipo-toxicity (the increased content of lipids within the RPE cell) is suggested to be a major factor affecting both the molecular mechanisms and the metabolic responses of the RPE cells leading to changes associated with drusen formation and ARMD pathology. To investigate this phenomenon, aged ARPE-19 cultures were induced to long term lipid loading with a free fatty acids (FFAs) mixture to ensures the increase of the intra-cellular lipid level within the cells. The accumulation of lipids was found to correlate with a destruction of the ARPE-19 monolayer integrity, an increase in VEGF-A secretion in media and most importantly the production of sub-RPE deposits positive for apolipoprotein E, vitronectin and Amyloid beta 1-42, all of which are prominent constituents of drusen, supporting the hypothesis of lipo-toxicity. To further investigate the effect of inflammation in ARMD, we introduced the aged ARPE-19 cell cultures to long term complement activation in the presence and absence of lipid loading. Complement activation showed protective response suggesting that the complement system plays a secondary modulating response role to a primary destructive initiator “lipid loading”. These findings suggest the use of aged ARPE-19 cell culture as a promising model for ocular aged related diseases study including drusen deposition mechanisms, while the use of ARPE-19 lipo-toxicity model will facilitate the analysis of molecular and cellular characteristics of ARMD pathogenesis, augmenting the therapeutic strategies for dry ARMD.